OUTCOME PREDICTION IN INDIVIDUALS WITH ORGANOPHOSPHORUS AND CARBAMATE POISONING: A PROSPECTIVE COHORT STUDY. - Kumar, Amit; Kumari, Sindhu; Tudu, Lalchand; Bhattacharya, Pradip Kumar; Raj, Kunal (Student's Journal of Health Research Africa, 2024)
Objective The study evaluated the predictive utility of Erythrocyte Acetylcholinesterase (E-AChE) and Butyrylcholinesterase (BChE) levels in individuals presenting with OP and carbamate poisoning. Methods Of the 60 patients, 42 had Organophosphorus (OP) poisoning, and 18 had Carbamate poisoning in the ER. Vital signs, symptoms, and POP Severity Scale scores were recorded. E-AChE levels were measured using the Rapid ChE Check Mobile, and BChE levels were assessed through standard lab techniques. SPSS was used for statistical analysis, examining correlations between E-AChE levels and outcomes like ICU stay, mechanical ventilation, and mortality. Results The study involved 60 patients (mean age 32.5 years, ± 10.7), 66.7% male and 33.3% female. Of these, 60% consumed OP chemicals and 40% carbamate. Severe poisoning was associated with significantly lower E-AChE levels (mean = 2.1 U/g Hb) compared to moderate (3.5 U/g Hb) and mild cases (5.1 U/g Hb) (p < 0.001), showing a strong negative correlation with POP Severity scores (rho = -0.76, p < 0.001). Butyrylcholinesterase (BChE) levels also showed a significant decrease in severe poisoning cases, aligning with clinical outcomes, although the correlation was less robust than with E-AChE. Delays in care led to severe consequences in 80% of low-income patients. Lower E-AChE levels correlated with prolonged ICU stays (r = -0.68, p < 0.001), increased ventilation needs (r = -0.62, p < 0.01), and higher mortality (r = -0.74, p < 0.001). Rural patients faced worse outcomes due to inadequate healthcare access. Conclusion Although BChE levels were also measured, their correlation with outcomes was less pronounced but still valuable. Incorporating early measurements of both E-AChE and BChE could enhance clinical decision-making in OP and carbamate poisoning cases. Recommendations Incorporating rapid diagnostic tools for cholinesterase measurement in emergency settings could improve clinical decision-making and patient outcomes.